2015
DOI: 10.1002/2015ja021972
|View full text |Cite
|
Sign up to set email alerts
|

The dawn enhancement of the equatorial ionospheric vertical plasma drift

Abstract: Previous studies have reported that a dawn enhancement does not present in the statistical picture of the equatorial ionospheric vertical plasma drift, while it clearly shows in case measurements. In this statistical study, it is the first time to investigate the occurrence of the dawn enhancement in the equatorial ionospheric vertical plasma drift from ROCSAT‐1 observations during geomagnetic quiet times. The dawn enhancements occur most frequently in June solstice and least frequently in December solstice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 45 publications
10
45
0
Order By: Relevance
“…1). However, in agreement with our results, a number of studies based mainly on satellite observations have reported anomalous enhancements of eastward electric fields near sunrise in the equatorial ionosphere, seasonally correlated with the sign of the magnetic declination at the point of observation (Aggson et al, 1995;Kelley et al, 2014;Zhang et al, 2015).…”
Section: The Sunrise Effectsupporting
confidence: 93%
See 1 more Smart Citation
“…1). However, in agreement with our results, a number of studies based mainly on satellite observations have reported anomalous enhancements of eastward electric fields near sunrise in the equatorial ionosphere, seasonally correlated with the sign of the magnetic declination at the point of observation (Aggson et al, 1995;Kelley et al, 2014;Zhang et al, 2015).…”
Section: The Sunrise Effectsupporting
confidence: 93%
“…The enhancement of the integrated zonal electric field related to the proposed dynamo mechanism attains its largest values when the sunrise terminator is aligned with the magnetic meridian. In central South America, this condition prevails during a period close to the December solstice, when there is a seasonal maximum in the intensity of the secondary zonal electric fields associated with the negative magnetic declination (Zhang et al, 2015). This corresponds exactly to the period in which our measurements were taken.…”
Section: The Sunrise Effectmentioning
confidence: 62%
“…However, in agreement with our results, a number of studies based mainly on satellite observations have reported anomalous enhancements of eastward electric fields near sunrise in the equatorial ionosphere, seasonally correlated with the sign of the magnetic declination at the point of observation (Aggson et al, 1995;Kelley et al, 2014;Zhang et al, 2015).…”
Section: The Sunrise Effectsupporting
confidence: 93%
“…Among aforementioned abnormal phenomena, the upward drift around dawn, opposite to its climatology, has been observed frequently (Aggson et al, 1995; Kelley et al, 2014; Woodman, 1970). Its occurrence rate reaches as high as ~1/3 (Zhang et al, 2015), and such high occurrence rate is likely associated with the appearance of large day‐to‐day variability since the high occurrence of upward drifts and the large day‐to‐day variability are both caused by frequent day‐to‐day changes of the electric field. In previous investigations, the day‐to‐day variability is generally quantified by standard deviations in one specific time window.…”
Section: Introductionmentioning
confidence: 99%